Alleviation methods to combat toxic impact of saline water irrigation for growing tomato (Solanum lycopersicum) - Hassan, Zilla; Sarwar, Ghulam; Sarfraz, Muhammad; Manzoor, Muhammad Zeeshan; Ashraf, Manaim (Journal of Pure and Applied Agriculture, 2025)
An appropriate experimental site was selected for the collection of soil after laboratory analysis. This experiment, comprised of 3 variable factors to be tested; first test factor was saline water of different qualities having EC (electrical conductivity) of 1, 2 and 3 dSm-1 Water (W1), Water (W2) and Water (W3), which were applied at different rates (Normal irrigation level (IL1) and 10% lesser irrigation level (IL2) in order to save water as well as salt addition occurring from saline water. The third test factor was mulching (plastic or crop residues, M2 and M3 respectively) against no mulching (M1). The objective was to reduce evaporation resulting in lesser crop water requirements and decreased salt accumulation through decreased irrigation. All treatments were replicated thrice with completely randomized design (CRD) of statistics growing tomato crop. Saline waters of varying levels were prepared artificially and applied according to treatment proposal. Mulching was also applied to different pots according to treatment plan. Uniform dose of NPK fertilizers were used to meet nutrient requirements of plants. There was complete maintenance and protection of tomatoes from diseases and insects by appropriate measures. Irrigation with saline water started after two weeks of tomato transplanting to ensure the establishment of plants. At tomato maturity, plant sampling was taken from all pots for laboratory determinations. All the data were processed statistically using appropriate procedures. Data indicated that maximum plant height, fresh weight/yield, dry weight mass, plant diameter, number of tomato fruits/plant as well as highest amounts of N, P and K in tomato plants were noted when water having EC less than 1.0 dSm-1 was used at normal rate and coupled with crop residues mulching. Through these techniques farmers can grow vegetables, especially tomato using poor quality water without any salt hazards.